The Carnivore Diet and Gut Health: Mechanisms, Benefits and Risks - Tuteja, Aleksander; Trala, Katarzyna; Więcko, Laura; Olczyk, Liwia; Burzykowska, Klaudia; Gęborys, Kamila; Tyla, Mikołaj; Mohaissen, Rema; Stabrawa, Patryk; Krupa, Konrad (Quality in Sport, 2025)
Introduction: The carnivore diet, composed exclusively of animal-sourced foods, has gained attention both as a nutritional trend and as a potential therapeutic strategy for gastrointestinal conditions. It excludes plant-based foods, resulting in markedly reduced carbohydrate and fiber intake. While some studies suggest clinical benefits, the underlying mechanisms and long-term safety remain controversial. Aim of the study: This review aims to evaluate the effects of the carnivore diet on gut health by exploring its physiological mechanisms, clinical benefits in intestinal diseases, and associated risks. Materials and Methods: A literature review was conducted, analyzing data on the carnivore diet's influence on gut microbiota, inflammatory markers, nutrient status, and clinical outcomes in conditions such as inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), and small intestinal bacterial overgrowth (SIBO). Publications from 2005 to 2025 were analyzed, with the majority from 2020 to 2024. Results: Evidence suggests that ketone bodies produced on a carnivore diet modulate inflammation through macrophage polarization and epigenetic pathways. Some case reports indicate symptom improvement in IBD and IBS, potentially due to reduced dietary antigens and fermentable carbohydrates. However, the diet’s exclusion of fiber impacts microbiome composition and short-chain fatty acid production, posing risks to mucosal integrity. Additionally, high consumption of red and processed meats may elevate cancer risk due to carcinogenic compounds and hormonal additives. Conclusions: While the carnivore diet may offer symptomatic relief in selected gastrointestinal disorders, its restrictive nature, potential nutrient deficiencies, and long-term health risks necessitate further controlled studies. Clinical implementation should be approached cautiously and under professional supervision.